3b + 2a = 2 and -2 + a = 8
-2 + a = 8 can be rearranged to show a = 8 + 2 = 10 (Effectively 2 has been added to both sides.)
As a = 10, the value for a can now be substituted in the equation 3b + 2a = 2
3b + 2x10 = 2 : 3b + 20 = 2 this can be rearranged to show 3b = 2 - 20 = -18
and dividing both sides by 3 gives b = -6.
3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b
1a+3b 2a+4b=3a +7b
(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b
11a+7b-(3b-2a)
your expression is this... 2a+3b with the information given you can not solve this problem . There is no information given whatsoever that in any way constrains the value of 'a' or 'b'. They can be anything you want them to be.
2ab - 3b2 - 3b + 2a does not have a solution, as it is not an equation.
3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b
2A plus 3B times 2A - 3B = 4A2 - 9B2; this is an example of the general formula (a + b)(a - b) = a2 - b2.
(2a + b)(a + 3b)
12a + 6b + 6c = 6(2a + b + c)
With the assumption your asking what a or b are in terms of each other. a=3b/(6b-2) b=2a/(6a-2)
1a+3b 2a+4b=3a +7b
(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b
11a+7b-(3b-2a)
your expression is this... 2a+3b with the information given you can not solve this problem . There is no information given whatsoever that in any way constrains the value of 'a' or 'b'. They can be anything you want them to be.
add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
8b -2a